Reservoir cascades in sequence and their effect in water reflectance - Pereira Filho, Waterloo; Wachholz, Flavio [UNESP]; Wiggers, Monica Marlise; Trentin, Aline; Faria Barbosa, Claudio Clemente; Misra, S. C.; Revetria, R.; Sztandera, L. M.; Iliescu, M.; Zaharim, A.; Parsiani, H. (World Scientific And Engineering Acad And Soc, 2008)
The modification of a river in several reservoirs with purpose of hydroelectric power provides important environmental modifications in the aquatic system. In this sense, this work has the objective of identifying the optical water modifications in the reservoirs located in the Jacui River in the state of Rio Grande do Sul in southern of Brazil. The reservoirs studied were: Passo Real with 221 km(2) and Dona Francisca with 21 km(2). Spectra of reflectance were obtained in these reservoirs with the use of the Fieldspec Spectroradiometer for spectra range between 400 to 900 nm. The transparency (obtained by Secchi Disc) was obtained. The reservoir of Passo Real presents minor transparency with domain of the brown color however the green color was observed in Dona Francisca. In both cases the impact of the water color in the spectra of reflectance was identified, being that Passo Real presented high reflectance in the green and red ranges of the electromagnetic spectrum whereas the Dona Francisca presented higher reflectance in the green region. Passo Real reservoir upstream localization was the main factor for determining the higher reflectance of water.
Keywords: Remote Sensing; Limnology; Field Spectra; Reservoir; the Jacui River; Brazil